A method for preparing a composite bonded structure for marine corrosion protection

CN122879668APending Publication Date: 2026-10-09CHINA UNIV OF GEOSCIENCES (WUHAN)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610642031.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

这种处理方式只实现了部分侵蚀性离子和水分子的隔离,当出现涂层破裂时会失效

Benefits of technology

(1)本发明大大降低了对加工设备和材料的要求,加工设备稳定性和效率高,加工材料简单安全性高,硅烷处理利用气相沉积,粘接结构加工简易,成本更低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879668A_ABST
    Figure CN122879668A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a composite bonding structure for marine corrosion prevention, and realizes the synergistic strengthening of mechanical interlocking, chemical bonding and corrosion path blocking of a bonding interface through the cross-scale coupling design of etching, vapor deposition and nano-enhanced modification. A three-dimensional microstructure of multidirectional intersection is etched on the surface of a base material, mechanical interlocking is realized to improve the connection strength and increase the silane area; then a dense silane film is formed on the surface of the base material through vapor deposition to construct stable chemical bonds between the base material and the adhesive; the modified nano-clay is uniformly dispersed in the resin adhesive, and the high aspect ratio of the nano-sheets is used to block the penetration of corrosive media; after bonding and curing, secondary vapor deposition of silane is carried out at the edge of the joint to form an edge sealing barrier. The application has low process cost, can significantly improve the peel strength and long-term corrosion resistance of the bonding joint, and is suitable for the bonding protection of marine engineering equipment such as aluminum alloy and carbon fiber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cross-scale design and surface treatment technology, specifically to a method for preparing a composite adhesive structure for marine corrosion protection. Background Technology

[0002] Adhesive structures are widely used in shipbuilding, offshore platform construction, and other fields due to their advantages such as light weight, uniform stress distribution, and ability to connect dissimilar materials. However, water and corrosive ions in seawater environments can cause severe corrosion to adhesive joints, reducing their performance, service life, and even causing failure. Improving the marine corrosion resistance of adhesive structures can reduce economic losses and ensure production safety.

[0003] Corrosion protection processes for bonded structures currently include: anodizing, chemical treatment, adding nanofillers, and anti-corrosion coatings. Anodizing treatment includes chromic acid anodizing and phosphoric acid anodizing. Chromic acid anodizing produces a thin but very dense oxide film with good fatigue resistance. Although chromic acid has a certain corrosion inhibition effect, hexavalent chromium is toxic and poses a significant environmental hazard. Phosphoric acid anodizing produces a thick oxide film, but it is prone to stress concentration and microcracks under alternating marine loads.

[0004] Chemical treatment relies on chemical reactions to form a protective layer or alter the surface properties at the bonding interface. It is generally simpler and less expensive, and some processes can be directly applied to on-site construction. A common chemical treatment method involves using a gas-phase process to form a silane film at the bonding interface using a silane coupling agent. This method provides the bonding interface with more functional groups: one end forms a strong covalent bond with the hydroxyl groups on the metal surface, while the other end reacts chemically with the adhesive (epoxy resin). The chemical bonds formed by silane are much more stable than simple physical adsorption, effectively preventing water molecules and corrosive ions from penetrating into the bonding interface. However, this treatment is too simplistic and cannot provide structural support. In bonding joints subjected to extremely high shear or impact forces, the weak chemical conversion layer may become the "weakest link" in the entire structure, eventually leading to interlayer tearing. Furthermore, the silane films obtained through chemical treatment are typically nanometer to micrometer-sized, and such thin films offer almost no wear resistance. In marine engineering construction, even minor scratches, collisions, or abrasion from sea sand can directly penetrate the protective layer, exposing the substrate to the marine environment and triggering electrochemical corrosion.

[0005] Anti-corrosion coatings typically consist of three parts: a primer layer, an intermediate coat, and a topcoat layer. When adhesives come into contact with the anti-corrosion coating, chemical incompatibility may occur, leading to peeling. Current practices involve bonding first, followed by overall coating; or leaving a "masking zone" in the bonding area to ensure the adhesive acts directly on the treated substrate, while the coating covers its edges. This approach only achieves partial isolation from corrosive ions and water molecules, and will fail when the coating cracks. Furthermore, this method does not improve the performance of the bonded structure and cannot mitigate fracture failure under alternating seawater loads. Summary of the Invention

[0006] The purpose of this invention is to provide a low-cost, high-performance corrosion-resistant adhesive structure. It achieves dual protection of mechanical interlocking and chemical bonding between silane and resin through the coupling effect of silane treatment and laser etching, and utilizes nano-clay to achieve the purpose of reinforcing phase blocking corrosion paths and enhancing adhesive performance.

[0007] To achieve the above objectives, the following technical solution is adopted: A method for preparing a composite adhesive structure for marine corrosion protection includes the following steps: (1) Substrate pretreatment: A three-dimensional microstructure is etched on the substrate bonding surface using methods such as laser processing, mechanical scribing or chemical etching; (2) Initial silane treatment: A first silane film is formed on the surface of the etched substrate by vapor deposition. (3) Adhesive preparation: The modified nano-reinforcing phase is uniformly dispersed into the adhesive matrix; (4) Bonding and secondary treatment: The substrate is bonded together using the adhesive prepared in step (3). After curing, a second silane film is deposited on the exposed surface of the bonded joint.

[0008] Furthermore, in step (1), the substrate is an aluminum alloy plate, a carbon fiber composite plate, or other adhesive materials.

[0009] Furthermore, in step (1), the etching parameters of the three-dimensional microstructure include: the etching pattern is a multi-directional cross-etching mark such as "+", "X" and "meter"; the line spacing is 0.1mm-0.4mm.

[0010] Furthermore, in step (2), the first silane film is prepared by vapor deposition at a reaction temperature above 80°C, and the silane reagent is hydrolyzed before use.

[0011] Furthermore, in step (3), the nano-reinforcing phase includes, but is not limited to, nano-clay, carbon nanotubes, nano-silica or graphene nanosheets, with a mass fraction of 1%wt-4%wt; the nano-clay is pre-treated with silane coupling agent or quaternary ammonium salt modification.

[0012] Furthermore, in step (3), the nano-reinforcing phase is introduced into the adhesive by vibration dispersion, mechanical stirring or ultrasonic dispersion.

[0013] Furthermore, in step (4), the second layer of silane film covers the edge gaps of the adhesive joint, forming a physical-chemical barrier that blocks moisture and corrosive ions.

[0014] Furthermore, the silane reagent includes, but is not limited to, one or a mixture of two of KH550 and KH560.

[0015] Furthermore, by adjusting the laser etching power and line spacing, silane solution concentration, nano-clay content, and vibration dispersion time, cross-scale coupling of mechanical interlocking and chemical bonding at the bonding interface can be achieved.

[0016] Furthermore, the adhesive includes, but is not limited to, epoxy resin adhesives, polyurethane adhesives, and vinyl ester resins.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) The present invention greatly reduces the requirements for processing equipment and materials. The processing equipment is stable and efficient, the processing materials are simple and safe, the silane treatment utilizes vapor deposition, the bonding structure is easy to process, and the cost is lower.

[0018] (2) This invention can efficiently prepare multi-bonded connection interfaces with coupling effects. By laser etching, the two-dimensional connection interface is extended to three dimensions, which increases the obstruction of water molecule diffusion paths and increases the silane interaction area, making it more conducive to the formation of chemical bonds between the connection interfaces and thus making its anti-corrosion performance stronger. (3) The etching structure of the interface in this invention can be adjusted by changing the etching power, pattern and line spacing of the marking machine, and the resulting etching structure is more complex, which can meet the needs of more fields to a certain extent. (4) This invention can process more types and more quantities of samples at the same time, has strong universality and huge application potential. Attached Figure Description

[0019] Figure 1 This is a process flow diagram of a method for preparing a composite adhesive structure for marine corrosion protection according to the present invention; Figure 2 The microstructure obtained by laser etching in Embodiment 2 of the present invention; Figure 3 This is the microstructure obtained by laser etching in embodiment 3 of the present invention. Detailed Implementation

[0020] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the technical solutions of this invention will be further described in detail below with reference to specific embodiments and accompanying drawings. Where specific test methods, instruments, and experimental conditions are not explicitly indicated in the embodiments, they are all performed in accordance with existing technologies known in the art, technical specifications recorded in relevant literature, or instrument / reagent product instructions; where the manufacturers of reagents, consumables, and instruments are not specified, they are all standard products that can be obtained through conventional commercial channels.

[0021] A method for preparing a composite adhesive structure for marine corrosion protection includes the following steps: (1) A three-dimensional structure is etched on the surface of the substrate using a marking machine; (2) A silane film is formed on the surface of a substrate using a vapor phase method; (3) Adjust the vibration parameters to uniformly disperse the enhanced nanophase into the adhesive; (4) After the adhesive joint is connected, a silane film is deposited on the surface.

[0022] Specifically, the marking machine mentioned in step 1 has the function of adjusting laser power, line spacing and pattern, and the required three-dimensional structure is easy to fill with adhesive.

[0023] Specifically, in step 1, the surface of the etched substrate needs to be easy to etch into a three-dimensional structure, and the three-dimensional structure needs to have a certain depth or span to be easy to fill with adhesive.

[0024] Specifically, the silane reagent in step 2 is hydrolyzed before use.

[0025] Specifically, the silane treatment method in step 2 is vapor deposition, and the airtightness and reaction temperature are kept above 80°C during the treatment.

[0026] Specifically, in step 3, the nano-clay needs to be pretreated with silane or quaternary ammonium salt before use.

[0027] Specifically, in step 3, the dispersion method is either vibration dispersion or stirring dispersion.

[0028] Specifically, in step 4, it should be ensured that the edge of the bonding interface has a silane film of sufficient thickness.

[0029] Specifically, the generation of target micro / nano structures is adjusted by modifying the shape and size of the processing container, the amplitude, frequency and direction of the vibration drive system, the curing conditions, and the viscosity and volume of the resin material.

[0030] The present invention finds through research that increasing the number of chemical bonds between bonding interfaces can improve the anti-corrosion performance of bonded joints. There are many parameters that restrict the number of chemical bonds at the bonding interfaces, including etching conditions (laser etching power, line spacing, pattern), silane parameters (type and content of silane, treatment time), etc. By adjusting the parameters, chemical bonds with different contents can be formed between the bonding interfaces. If a nano-clay reinforcing phase is added to the adhesive, an anti-corrosion bonding structure can be formed under the combined action of silane chemical bonds and the nano reinforcing phase.

[0031] The present invention uses silane to generate chemical bonds, which acts on the bonding surface between the resin of the bonded joint and the base material after adjusting etching and chemical parameters. The target bonding structure is generated by adjusting parameters including etching power, line spacing, silane concentration, silane type and treatment time simultaneously. Meanwhile, a nano reinforcing phase is introduced into the adhesive to block the diffusion of water molecules and enhance the strength of the bonded joint, thereby generating an anti-corrosion bonded joint. By changing the parameters of the nano reinforcing phase and using laser etching to increase the action area of silane, the number of chemical bonds is increased, so as to achieve the purpose of obtaining a cross-dimensional anti-corrosion bonding structure.

[0032] Example 1 A preparation method of a composite bonding structure for marine anti-corrosion, comprising the following steps: S1. Prepare a carbon fiber plate and an aluminum plate with dimensions of 100mm*100mm*25mm (the carbon fiber plate is made of carbon fiber woven fabric and epoxy resin 105, with an elastic modulus of 160, density: ; the aluminum plate is of model 6601, with an aluminum content > 97.299%, an elastic modulus of 70, and a density of 2.7g / cm³).

[0033] S2. Preparation before laser treatment: place the carbon fiber plate and the aluminum plate in an ultrasonic cleaner for cleaning for twenty minutes to remove oil stains and dust on the surfaces, then put the cleaned plates into an oven and dry them at 60°C for ten minutes.

[0034] S3. Plate fixing: fix the aluminum plate on a marking machine with a special fixture, adjust the position of the aluminum plate to ensure that the laser focus of the marking machine and the surface of the aluminum plate are on the same plane.

[0035] S4. Laser etching preparation: use a 10W red laser, turn on the light source for preheating in advance, and adjust the focusing and the laser etching range.

[0036] S5. Turn on the laser etching system: adjust the etching pattern to a "rice" shape, select a line spacing of 0.2mm, and set the number of scans to 6. The etched structure is as shown in Figure 2 .

[0037] S6, Pre-silane treatment preparation: preparing a silane solution, wherein the selected silane is KH560, and the silane solution consists of 4% silane reagent, 6% aqueous solution and 90% methanol. After fully stirring the silane solution, the silane reagent is directly treated by vapor deposition.

[0038] S7, Silane reagent treatment: heating the prepared silane solution at 80°C, collecting silane gas by gas collection method, placing the plate therein and heating for 30 minutes, and bonding with an adhesive after full reaction.

[0039] S8, Addition of nano-reinforcement phase: stirring and dispersing the modified nano-clay into the adhesive, wherein the mass fraction of nano-clay is 4%wt.

[0040] Example 2 A preparation method of a composite bonding structure for marine corrosion protection, comprising the following steps: S1, preparing a carbon fiber plate and an aluminum plate with dimensions of 100mm*100mm*25mm (the carbon fiber plate is made of carbon fiber woven fabric and epoxy resin 105, with an elastic modulus of 160 and a density of ; the aluminum plate has a model of 6601, with an aluminum content >97.299%, an elastic modulus of 70, and a density of 2.7g / cm³). S2, Pre-laser treatment preparation: placing the carbon fiber plate and the aluminum plate in an ultrasonic cleaning machine for cleaning for 20 minutes to remove oil stains and dust on the surfaces, then putting the cleaned plates into an oven and drying at 60°C for 10 minutes.

[0041] S3, Plate fixing: fixing the aluminum plate on a marking machine with a special fixture, adjusting the position of the aluminum plate to ensure that the laser focus of the marking machine and the surface of the aluminum plate are on the same plane.

[0042] S4, Pre-laser etching preparation: adopting a 15W red laser, turning on the light source in advance for preheating, and adjusting the focusing and the laser etching range.

[0043] S5, starting the laser etching system: adjusting the etching pattern to a "cross" shape, selecting a line spacing of 0.4mm and setting the number of scanning to 4, and the etching structure is as shown in Figure 3 .

[0044] S6, Pre-silane treatment preparation: preparing a silane solution, wherein the selected silane is KH550, and the silane solution consists of 3% silane reagent, 7% aqueous solution and 90% methanol. After fully stirring the silane solution, the silane reagent is directly treated by vapor deposition.

[0045] S7, Silane reagent treatment: heating the prepared silane solution at 80°C, collecting silane gas by gas collection method, placing the plate therein and heating for 30 minutes, and bonding with an adhesive after full reaction.

[0046] S8. Addition of nano-reinforcing phase: The modified nano-clay is dispersed in the binder by stirring, and the mass fraction of nano-clay is 2%wt.

[0047] Where there is no conflict, the above embodiments and features described herein can be combined with each other.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a composite adhesive structure for marine corrosion protection, characterized in that, Includes the following steps: (1) Substrate pretreatment: A three-dimensional microstructure is etched on the substrate bonding surface using methods such as laser processing, mechanical scribing or chemical etching; (2) Initial silane treatment: A first silane film is formed on the surface of the etched substrate by vapor deposition. (3) Adhesive preparation: The modified nano-reinforcing phase is uniformly dispersed into the adhesive matrix; (4) Adhesion and secondary treatment: The substrate is bonded together using the adhesive prepared in step (3). After curing, a second silane film is deposited on the exposed surface of the bonded joint.

2. The method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: In step (1), the substrate is an aluminum alloy plate, a carbon fiber composite plate, or other adhesive materials.

3. The method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: In step (1), the etching parameters of the three-dimensional microstructure include: the etching pattern is a multi-directional cross etching mark such as "+", "X" and "meter"; the line spacing is 0.1mm-0.4mm.

4. The method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: In step (2), the first silane film is prepared by vapor deposition at a reaction temperature above 80°C, and the silane reagent is hydrolyzed before use.

5. The method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: In step (3), the nano-reinforcing phase includes one or more of nano-clay, carbon nanotubes, nano-silica or graphene nanosheets, and the mass fraction of the nano-reinforcing phase is 1%wt-4%wt; the nano-clay is pre-treated with silane coupling agent or quaternary ammonium salt modification.

6. The method for preparing a composite adhesive structure for marine corrosion protection as described in claim 1, characterized in that: In step (3), the nano-reinforced phase is introduced into the adhesive by vibration dispersion, mechanical stirring or ultrasonic dispersion.

7. The method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: In step (4), the second layer of silane film covers the edge gaps of the adhesive joint, forming a physical-chemical barrier that blocks moisture and corrosive ions.

8. The method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: The silane reagent includes one or a mixture of two of KH550 and KH560.

9. The method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: By adjusting etching parameters, structural line spacing, silane solution concentration, nano-clay content, and vibration dispersion time, cross-scale coupling of mechanical interlocking and chemical bonding at the bonding interface is achieved.

10. A method for preparing a composite adhesive structure for marine corrosion protection according to claim 1, characterized in that: The adhesive includes one or more of epoxy resin adhesives, polyurethane adhesives, and vinyl ester resins.